Poverty, vulnerability, and reference dependent utility - Isabel Günther; Johannes Maier (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
In this paper we argue that the recent evidence on individuals' decision making is of high relevance for the measurement of poverty when switching from a static and certain to a dynamic and uncertain framework. The numerous proposed measures of multi-period poverty and vulnerability have until now not taken into account the insights from behavioural economics. Building on reference dependent utility models we propose a new measure of both (perceived) multi-period poverty and vulnerability, where the poverty status of an individual is not only a function of (expected) consumption levels but also of (expected) losses and gains in consumption. We demonstrate the implications of the proposed measures with a small illustrative example.
Keywords: D60; D81; I32; 330; multi-period poverty; vulnerability; reference dependent utility; prospect theory; loss aversions